Early Ischemic Stroke Assessment with ASPECTS: A Case Report Highlighting the Radiologist's Role in a Limited-Resource Setting - I Made Andika Adiguna; Nyoman Satya; Ni Putu Popy Theresia Puspita (HM Publisher, 2025)
Background: Ischemic stroke is a leading cause of morbidity and mortality globally, particularly in resource-limited settings. Non-contrast computed tomography (NCCT) is often the primary imaging modality available in these settings, and the Alberta Stroke Program Early CT Score (ASPECTS) is a crucial tool for assessing early ischemic changes in NCCT. This case report highlights the importance of ASPECTS in guiding clinical decisions and prognostication in a resource-limited setting. Case presentation: A 79-year-old male presented to the emergency unit at Negara General Hospital, a rural facility in Bali, with acute onset of right-sided hemiparesis and speech difficulty. NCCT showed a hypodense lesion with ill-defined margins in the left insular cortex, left caudate nucleus, left internal capsule, and left frontotemporoparietal lobes, consistent with a subacute cerebral infarction in the middle cerebral artery (MCA) territory, with an ASPECTS score of 2. Due to the extensive ischemic burden and the limited availability of advanced treatment options, conservative management was chosen. The radiologist's interpretation of the ASPECTS score played a critical role in guiding the clinical team's decision-making and informing the patient's family about the prognosis. Conclusion: ASPECTS is an essential tool for predicting stroke outcomes, with lower scores correlating with larger infarct volumes and poorer prognoses. In resource-limited settings, radiologists play a vital role in interpreting ASPECTS scores to guide clinical management and provide accurate prognostic information to patients and their families.